Analisis Tindak Tutur Direktif dan Ekspresif pada Artikel Rubrik dalam Surat Kabar Daring Kompas.Id Edisi Tahun 2020 dan Rekomendasinya pada Pembelajaran Bahasa Indonesia - Harahap, Cindy Angelina; Hidayat, Dayat; Dinar Pratiwi, Wienike (Jurnal Pendidikan : Riset dan Konseptual, 2025)
The research "Analysis of Directive and Expressive Speech Acts in Section Articles on Kompas.id Online Newspaper Edition 2020 and Its Recommendations for Indonesian Language Learning" aims to investigate and gather information regarding directive and expressive speech acts in section articles on the Kompas.id online newspaper edition of 2020, and their recommendations for Indonesian language learning. Directive speech acts include: (1) advising, (2) requesting, (3) commanding, (4) suggesting, (5) challenging, (6) urging, (7) inviting, (8) asking. Meanwhile, expressive speech acts include: (1) criticizing, (2) praising, (3) complaining, (4) congratulating, (5) expressing gratitude, (6) blaming, (7) apologizing. Through directive and expressive speech acts, the author hopes that teachers can utilize these speech acts in classroom learning interactions. This research aims to explain the types of directive and expressive speech acts used by teachers and student.